CO oxidation activity of Pt, Zn and ZnPt nanocatalysts: a comparative study by in situ near-ambient pressure X-ray photoelectron spectroscopy. Issue 14 (26th March 2018) - Naitabdi, Ahmed; Boucly, Anthony; Rochet, François; Fagiewicz, Robert; Olivieri, Giorgia; Bournel, Fabrice; Benbalagh, Rabah; Sirotti, Fausto; Gallet, Jean-Jacques
Abstract : NAP-XPS allows the monitoring of chemical reactions on nanocatalysts. Abstract : The investigation of nanocatalysts under ambient pressure by X-ray photoelectron spectroscopy gives access to a wealth of information on their chemical state under reaction conditions. Considering the paradigmatic CO oxidation reaction, a strong synergistic effect on CO catalytic oxidation was recently observed on a partly dewetted ZnO(0001)/Pt(111) single crystal surface. In order to bridge the material gap, we have examined whether this inverse metal/oxide catalytic effect could be transposed on supported ZnPt nanocatalysts deposited on rutile TiO2 (110). Synchrotron radiation near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) operated at 1 mbar of O2  : CO mixture (4 : 1) was used at a temperature range between room temperature and 450 K. To tackle the complexity of the problem, we have also studied the catalytic activity of nanoparticles (NPs) of the same size, consisting of pure Pt and Zn nanoparticles (NPs), for which, moreover, NAP-XPS studies are a novelty. The comparative approach shows that the CO oxidation process is markedly different for the pure Pt and pure Zn NPs. For pure Pt NPs, CO poisoned the metallic surfaces at low temperature at the onset of CO2 evolution. In contrast, the pure Zn NPs first oxidize into ZnO, and trap carbonates at low temperature. Then they start to release CO2 in the gas phase, at a critical temperature, while continuously producing it. The pure Zn NPs are also immune to support encapsulation. The bimetallic nanoparticle borrows some of its characteristics from its two parent metals. In fact, the ZnPt NP, although produced by the sequential deposition of platinum and zinc, is platinum-terminated below the temperature onset of CO oxidation and poisoned by CO. Above the CO oxidation onset, the nanoparticle becomes Zn-rich with a ZnO shell. Pure Pt and ZnPt NPs present a very similar activity towards CO oxidation, in contrast with what is reported in a single crystal study. The present study demonstrates the effectiveness of NAP-XPS in the study of complex catalytic processes at work on nanocatalysts under near-ambient pressures, and highlights once more the difficulty of transposing single crystal surface observations to the case of nanoobjects.